Structure and physicochemical characterization of a naproxen–picolinamide cocrystal. Issue 3 (6th February 2017) - Kerr, Hannah E.; Softley, Lorna K.; Suresh, Kuthuru; Hodgkinson, Paul; Evans, Ivana Radosavljevic
Abstract : The crystal structure is reported of a new 1:1 cocrystal of naproxen with picolinamide, and the pharmaceutically relevant properties are investigated. An NMR crystallography approach is used to distinguish between two crystallographically unique COOH–CONH hydrogen‐bonded dimers and to confirm the location of the H atoms in the two dimers. Abstract : Naproxen (NPX) is a nonsteroidal anti‐inflammatory drug with pain‐ and fever‐relieving properties, currently marketed in the sodium salt form to overcome solubility problems; however, alternative solutions for improving its solubility across all pH values are desirable. NPX is suitable for cocrystal formation, with hydrogen‐bonding possibilities via the COOH group. The crystal structure is presented of a 1:1 cocrystal of NPX with picolinamide as a coformer [systematic name: ( S )‐2‐(6‐methoxynaphthalen‐2‐yl)propanoic acid–pyridine‐2‐carboxamide (1/1), C14 H14 O3 ·C6 H6 N2 O]. The pharmaceutically relevant physical properties were investigated and the intrinsic dissolution rate was found to be essentially the same as that of commercial naproxen. An NMR crystallography approach was used to investigate the H‐atom positions in the two crystallographically unique COOH–CONH hydrogen‐bonded dimers. 1 H solid‐state NMR distinguished the two carboxyl protons, despite the very similar crystallographic environments. The nature of the hydrogen bonding was confirmed by solid‐state NMR and density functional theory calculations.